2019
DOI: 10.18280/acsm.430603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrafine Ground Granulated Blast-Furnace Slag (UFGGBFS) and Copper Slag on Ambient Cured Geopolymer Concrete

Abstract: This paper explores deep into the effects of mineral admixtures, e.g. ultrafine ground granulated blast-furnace slag (UFGGBFS) and copper slag (CPS), on ambient cured geopolymer concrete (GPC). First, a GPC was prepared from mineral admixtures like the UFGGBFS, fly ash and the CPS, and alkali activators like sodium hydroxide (NaOH) and sodium silicate (Na2SiO3). Then, 10M, 12M and 14M GPC samples were created, with UFGGBFS content of 0%, 5%, 10% and 15%, respectively. These samples were subjected to compressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Drawing on the previous studies, this paper analyzes the diagenesis of the Permian tight sandstone reservoirs in Gubei low buried hill, Jiyang Depression, and discusses the coupling between buried hill tectonic activity and diagenetic evolution. The following analysis and testing methods were adopted to facilitate the research: core observation, casting sheet observation, X-ray diffractometry (XRD) (Hadi et al 2019;Rathanasalam et al 2019;Yan et al 2020), scanning electron microscopy (SEM) (Al Owais and El-Hallag 2020;Merizgui et al 2019;Wang et al 2019), and energy spectrum analysis. The research results provide a reference for the exploration and development of clastic buried hills.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on the previous studies, this paper analyzes the diagenesis of the Permian tight sandstone reservoirs in Gubei low buried hill, Jiyang Depression, and discusses the coupling between buried hill tectonic activity and diagenetic evolution. The following analysis and testing methods were adopted to facilitate the research: core observation, casting sheet observation, X-ray diffractometry (XRD) (Hadi et al 2019;Rathanasalam et al 2019;Yan et al 2020), scanning electron microscopy (SEM) (Al Owais and El-Hallag 2020;Merizgui et al 2019;Wang et al 2019), and energy spectrum analysis. The research results provide a reference for the exploration and development of clastic buried hills.…”
Section: Introductionmentioning
confidence: 99%
“…RCA addition upto 25 per cent provides good mechanical properties to the geopolymer concrete. Strength studies of GGBS and copper slag based geopolymer cured at ambient temperature (room temperature 25°C) for 56 days was studied (Rathanasalam et al , 2019). It was concluded that the strength increases with the increment of GGBS content even at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%